2022
DOI: 10.3390/land11020300
|View full text |Cite
|
Sign up to set email alerts
|

Catchment-Scale Participatory Mapping Identifies Stakeholder Perceptions of Land and Water Management Conflicts

Abstract: Competing socioecological demands and pressures on land and water resources have the potential to increase land use conflict. Understanding ecosystem service provisioning and trade-offs, competing land uses, and conflict between stakeholder groups in catchments is therefore critical to inform catchment management and the sustainable use of natural resources. We developed a novel stakeholder engagement methodology that incorporates participatory conflict mapping in three catchments with a short questionnaire to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 86 publications
0
1
0
Order By: Relevance
“…An examination of the key informants' perceptions of landscape justice provided insights into land and water management issues and revealed the need for participatory management approaches in the case of Atlantic salmon, which should be further developed. This is because participatory management approaches have shown potential across Europe and beyond to foster mutual understanding and increase local knowledge to inform decision making on the sustainable management of river catchments, including Atlantic salmon fishing activities [54,55]. We found that state governance affects the formation of, but is, therefore, also responsible for managing, the social, cultural, and economic risks.…”
Section: Discussionmentioning
confidence: 89%
“…An examination of the key informants' perceptions of landscape justice provided insights into land and water management issues and revealed the need for participatory management approaches in the case of Atlantic salmon, which should be further developed. This is because participatory management approaches have shown potential across Europe and beyond to foster mutual understanding and increase local knowledge to inform decision making on the sustainable management of river catchments, including Atlantic salmon fishing activities [54,55]. We found that state governance affects the formation of, but is, therefore, also responsible for managing, the social, cultural, and economic risks.…”
Section: Discussionmentioning
confidence: 89%
“…This is a significant achievement of the project, as it connects its outcomes with the respective regulatory and institutional frameworks that will determine the future water management of the BD. Efforts that lack this regulatory component (as well as its interaction with the participatory processes) have resulted in limited changes towards a more effective governance for sustainable water management [34,68].…”
Section: Co-development Of Recommendationsmentioning
confidence: 99%
“…Over the years, numerous approaches have been conducted to examine factors influencing the attitudes and behavior of stakeholders, drawing on theories from the social sciences, particularly in the management of hydrosocial territories (Ricart et al, 2019a). Widening participants' involvement in research can identify differences in opinion and understanding across communities, capture valuable local expertise, and facilitate knowledge exchange between stakeholders (Stosch et al, 2022). Participatory research approaches can also ensure that management decisions are more inclusive, socially acceptable, and effectively implemented.…”
Section: Introductionmentioning
confidence: 99%